PLANNING THE CONSTRUCTION OF DRAINAGE ALONG THE ROAD FROM BALUNIJUK VILLAGE TO JADA BAHRIN VILLAGE TO PREVENT WATER PONDING - Aulia Puspita Sari; Kartini; Izam Zamali; Eveline (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
This project aims to plan the construction of a drainage system along the road from Balunijuk Village to Jada Bahrin Village, Bangka Regency, to prevent waterlogging that often occurs during the rainy season. An adequate drainage system is expected to reduce road damage and minimize negative impacts on the environment, health, and activities of the local community. Financial studies show that this project is feasible to implement with a positive Net Present Value (NPV) of IDR4,777,274,281 at a 10% discount rate, and IDR4,226,951,979 at a 15% discount rate. The project's Internal Rate of Return (IRR) reaches 12.65%, while the Benefit-Cost Ratio (BCR) is 3.57, indicating that this project is very profitable.